2019
DOI: 10.1128/aac.01610-18
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Typing and Resistance Mechanism Analysis of Voriconazole-Resistant Aspergillus flavus Isolates in South Korean Hospitals

Abstract: A recent surveillance study in South Korea revealed that 14% (7/50) of Aspergillus flavus clinical isolates had a voriconazole minimum inhibitory concentration of ≥4 μg/ml. Of seven non-wild-type (non-WT) isolates, six ear isolates from four hospitals shared the same microsatellite genotype. None of the non-WT isolates showed cyp51 mutations associated with azole resistance. However, the mean expression levels of efflux pump (MDR2, atrF, and mfs1) and target (cyp51A) genes exhibited significant differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
0
22
1
1
Order By: Relevance
“…Microsatellite typing revealed that six of the seven non‐wild‐type isolates, which were obtained from ear specimens at four hospitals, shared the same microsatellite genotype. None of the non‐wild‐type isolates showed any cyp51 mutations associated with azole resistance, but the mean expression levels of efflux pumps ( MDR2 , atrF and mfs1 ) and target genes ( cyp51A ) exhibited significant differences between the non‐wild types and the other isolates . Continued testing of A flavus is relevant, as it is the second most common cause of IA and its burden of azole resistance has not been fully explored .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsatellite typing revealed that six of the seven non‐wild‐type isolates, which were obtained from ear specimens at four hospitals, shared the same microsatellite genotype. None of the non‐wild‐type isolates showed any cyp51 mutations associated with azole resistance, but the mean expression levels of efflux pumps ( MDR2 , atrF and mfs1 ) and target genes ( cyp51A ) exhibited significant differences between the non‐wild types and the other isolates . Continued testing of A flavus is relevant, as it is the second most common cause of IA and its burden of azole resistance has not been fully explored .…”
Section: Discussionmentioning
confidence: 99%
“…None of the non-wild-type isolates showed any cyp51 mutations associated with azole resistance, but the mean expression levels of efflux pumps (MDR2, atrF and mfs1) and target genes (cyp51A) exhibited significant differences between the nonwild types and the other isolates. 32 Continued testing of A flavus is relevant, as it is the second most common cause of IA and its burden of azole resistance has not been fully explored. 33 To the best of our knowledge, no study has yet demonstrated the association between azole-resistant clinical A flavus and environmental isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, A. flavus strains with MIC values higher than the epidemiological cutoff value established for voriconazole by CLSI, 1 mg/liter, were reported to sometimes harbor cyp51A, cyp51B, and cyp51C mutations, as A. flavus has three cyp51 genes. These strains presented different susceptibility patterns, as some of them had reduced susceptibility to all azoles (46) while others showed intermediate MIC values for itraconazole and posaconazole (11,13). Two A. flavus sensu stricto strains (6%) within the program were classified as itraconazole resistant, based on the EUCAST clinical breakpoint, and had high MICs against voriconazole, posaconazole, and isavuconazole.…”
Section: Discussionmentioning
confidence: 99%
“…Most A. fumigatus triazole resistance cases are explained by point mutations in the cyp51A gene, which encodes the 14␣-sterol-demethylase of the ergosterol biosynthesis pathway (10). Point muta-tions associated with azole resistance have also been reported in cyp51A in Aspergillus terreus and in cyp51C in Aspergillus flavus (11)(12)(13)(14)(15). Resistance in Aspergillus has also been described in cryptic or sibling species, which can only be identified to the species level using molecular tools and are classified in "complex" of closely related species when convenient identification techniques are not performed (16).…”
mentioning
confidence: 99%
“…Recently, A. flavus isolates with in vitro azole resistance have been described and azole resistance mechanisms in these strains are being analyzed. To date, different A. flavus Cyp51 point mutations have been described [ 22 , 23 , 24 , 25 , 26 ], however their role in azole resistance cannot be assumed since most of them were eventually described in azole susceptible strains. To date, only one point mutation (Y319H) in A. flavus Cyp51C seems to be related to azole resistance although it needs further confirmation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%